Molecular mechanism of inhibition of the mitochondrial carnitine/acylcarnitine transporter by omeprazole revealed by proteoliposome assay, mutagenesis and bioinformatics. - Annamaria Tonazzi; Ivano Eberini; Cesare Indiveri (PLoS ONE, 2013)
The effect of omeprazole on the mitochondrial carnitine/acylcarnitine transporter has been studied in proteoliposomes. Externally added omeprazole inhibited the carnitine/carnitine antiport catalysed by the transporter. The inhibition was partially reversed by DTE indicating that it was caused by the covalent reaction of omeprazole with Cys residue(s). Inhibition of the C-less mutant transporter indicated also the occurrence of an alternative non-covalent mechanism. The IC50 of the inhibition of the WT and the C-less CACT by omeprazole were 5.4 µM and 29 µM, respectively. Inhibition kinetics showed non competitive inhibition of the WT and competitive inhibition of the C-less. The presence of carnitine or acylcarnitines during the incubation of the proteoliposomes with omeprazole increased the inhibition. Using site-directed Cys mutants it was demonstrated that C283 and C136 were essential for covalent inhibition. Molecular docking of omeprazole with CACT indicated the formation of both covalent interactions with C136 and C283 and non-covalent interactions in agreement with the experimental data.